The Influence of Profitability, Leverage, and Firm Size on Firm Value with Dividend Policy as a Mediating Variable - Fitriya, Novi Rahma; Ernawati, Sri; Syahdan, Saifhul Anuar; Syam, Akhmad Yafiz (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study aims to analyse the effect of profitability, leverage, and firm size on firm value mediated by dividend policy. This study uses a purposive sampling method. This study includes non-cyclical industries on the Indonesia Stock Exchange for the period 2020-2023, with a population of 23 companies and a sample size of 125. The data were analysed and hypotheses tested using the Structural Equation Modelling Partial Least Squares (SEM-PLS). The findings of this study indicate that profitability, leverage and firm size have positive influences on firm value. Dividend policy has a significant direct effect on firm value. However, the indirect effect of independent variables through dividend policy was not significant.